(3bWY aj GdYed HGdUajMI GdRQbGdjIs - (3CHh Ydj TQa GdOjf GdMSf Hf Ydj Hf YeQ GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3gPg GddBdg CLd GdGdGJ hCTQagG dYehegG LejY GdCaGb hdCfgG JhUd Edi CehQ cKjQI Ldjdg s
(3BNQgG (B:s
(3heKGd eG cJHfG CHYGO GdeQGQGJ Yf eOGQ GdCSJhGA hGddg Gdehab s
(3eLghd GdCUds
(3agd gh ef cJGH LGeY GdeHGOF hGdZGjGJ ddeQGcTi ?s
(3hJTJed Ydi GdHGH GdQGHY (B- (3GdaUd GdKGdK , GdaUd GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B286s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B25 s
Keywords: (3Gdadcs